GAYA BAHASA DALAM LIRIK LAGU ALBUM CAN’T BUY MY LOVE KARYA YUI YOSHIOKA - Purba, Mega Yessica; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discussed This study discusses the types and meanings of language styles contained in the lyrics of the album Can’t Buy My Love by Yui Yoshioka. This study aims to identify the type of language style and that meaningin song lyrics. The method used in this study is a qualitative descriptive method using the Cognitive Linguistics approach proposed by Lakoff and Johnson. From the results of the analysis that has been discussed regarding the types pf figurative language. It is found that there are types of casual metonymy, ontological metaprhors, concepatual metaphors, simile part and whole metonymy and synecdoche. The language style has meanings related to psychology, the expression of fellings, time, events, life, depiction of objects, distance, space, owner, memory, atmosphere/condition.Key Words: Language style, lyrics of album Can’t Buy My Love. Meaning.